Magnetic oxides and composites II - Jotania, Rajshree B.; Mahmood, Sami H. (Materials research foundations ;, 2020)
The book focuses on the relevant basic concepts of Magnetic oxides, as well as on synthesis routes and important applications of spinel ferrites, hexaferrites and magnetic oxide nanomaterials